THE INFLUENCE OF FACILITIES, SERVICES, AND LOCATION ON THE INTEREST IN RETURN VISITS OF TOURISTS IN JUMA WILL DOKAN - Klaransia br Ginting; Edi Winata (Jurnal Ekonomi, 2023)
This study discusses the intention of visiting tourists again. This is based on a brief interview conducted with visitors at Juma Bakal Dokan. This research shows that there are indications of interest in returning visitors to the facilities, services, and locations provided. These problems are based on short interview observations aimed at visitors interested in visiting visitors again for the facilities, services, and locations provided. The long distance to the center of tourist attractions and the lack of implementation of smart home system innovations are indicated as a drawback. This study focuses on knowing whether there is an influence between facilities (X1) service (X2) location (X3) on tourists' intention to revisit (Y). This study used a quantitative descriptive method with multiple linear regression models as a data analysis model. Questionnaires were distributed to 67 visitors who were then processed using the SPSS 22 program. Testing the hypothesis in this study using the R2 test, t-test, and f-test. The results of this study indicate that there is a simultaneous influence between facilities, services, and location on intention to return. Based on the partial test, it was also found that there was a positive effect between facilities and services on tourists' intention to revisit Juma Bakal Dokan, but at the location, there was no effect on the intention to be revisited by tourists showing negative count results. Meanwhile, the magnitude of the influence between facilities and service quality on tourists' intention to revisit is 82%.